What Stuff Games are Made of? - Vladislav V. Kirichenko (Галактика медиа: журнал медиа исследований, 2024)
This article is a review of Pippin Barr’s book The Stuff Games Are Made Of (2023), which explores various elements of game worlds. Over the course of ten chapters, including introduction and conclusion, the author of the monograph examine samples with stable basic concepts of computer games and their production. Being a game designer and a theorist, Pippin Barr reflects on many ‘medianized’ aspects of computer games, such as goals and rules, calculations and algorithms, graphics and interface, time and space, cinematography prism, cruelty and violence, and monetarization.